EFFECTS OF SWEET BASIL (OCIMUM BASILICUM) LEAF POWDER ON THE SENSORY AND NUTRITIONAL QUALITIES OF BEEF AND FRANKFURTER SAUSAGES - Abu, A.; Adzitey, F. (UDS International Journal of Development, 2019)
The aim of the experiment was to find out the effects of sweet basil leaf powder on the sensory and nutritional qualities of beef and frankfurter sausages. The experiment involved the use of basil leaves powder at 4, 6 and 8g/kg meat in place of adobo®, a commercially formulated spice in both beef and frankfurter sausages. Sensory attributes such as colour, aroma, flavour intensity, flavour liking and texture were evaluated. The addition of basil leaves powder resulted in a significant (P<0.001) effect on the colour of both beef and frankfurter sausages. The control and 4g of the test materials in beef and frankfurter sausages had acceptable sensory attributes as compared to the higher levels (6 and 8g/kg). Sweet basil leaf powder did not have any adverse effect on the sensory characteristics of the products. There was significant difference (P<0.05) among treatment means in terms of fat content of the frankfurter sausages. However, the moisture and crude protein content of both beef and frankfurter sausages were not improved by the addition of basil leaf powder. Keywords: Sweet Basil, Beef Sausages, Frankfurter, Sensory, Minerals